Ourivesaria das coisas: os metais na arquitetura do mundo - Bortolotti, Bruna Albuquerque (2024)
I use goldsmithing, the craft I learned from my grandfather, to write this dissertation. This means: goldsmithing is my writing, research and invention methodology. It is starting from the goldsmith's craft that I investigate jewelry, desecrating (AGAMBEN, 2009) its meaning and displacing it from its European tradition, as an object made of stones and metals. In place of the object, I propose the jewelry as a thing (INGOLD, 2012; HEIDEGGER, 1987) related to the flows of the world, to social, political and material issues. The jewel is presented in this writing as an incarnated thing, which is characterized more by the tactility of the person who builds and uses it than by visuality. I propose an expanded understanding of the jewel, establishing a historicity that is not intended to be linear and seeking the origin of the thing without intending to find it: it is important, rather, to build what is fundamental in the jewel to transform it into this writing. I question what is stated as a movement (CAMPOS, 2011) of jewelry in contemporary times, the so-called jewelry art or contemporary jewelry, and I choose to take another path: practicing a goldsmithing of things. Therefore, I do not propose to make jewelry, but from goldsmithing to do other things, such as the writing that is presented. In this dissertation, I establish a relationship with authors who discuss jewelry, such as Passos (2018) and Unger (2017), authors who discuss the thing, such as Ingold (2012) and Heidegger (1987) and art historians, such as Archer (2001) and Cauquelin (2005). Philosophers Bennett (2010) and Han (2022) are present in this dissertation to support an approach to things and jewelry through the discussion of materiality. Through Albert and Kopenawa (2015), Iubel (2020) and the wisdom I build at the goldsmith's bench, metals infiltrate this dissertation and take on a life of their own, just as Deleuze and Guattari (1997) already stated about minerals such as privileged substance capable of exposing the vitality of materials.